Pericardial Tamponade and Elevated Serum CA-125 Level in Inadequately Treated Hypothyroidism - Moaaz Baghal; Viralkumar Amrutiya; Bhoomi Patel; Rutwik Patel; Jonathan Hernandez; Mohamed Ahmed; Abraham Lo; Mark Gabelman (Case Reports in Cardiology)
Cardiac tamponade is a medical emergency and must be managed promptly, and reaching a diagnosis is imperative to prevent recurrence. Herein, we present a case of a young female patient that presented with progressive shortness of breath and abdominal distension and was found to have cardiac tamponade with the finding of elevation of a blood tumor marker, CA-125, in the setting of nonadherence to thyroid replacement therapy. She was managed by surgical pericardial window and abdominal paracentesis, with replacement of thyroid hormones leading to resolution of the tamponade and ascites. CA-125 elevation associated with cardiac tamponade and myxedema ascites due to hypothyroidism is very rare, and we aim to shed light on the importance of having a broad differential when approaching cardiac tamponade and understand the association between CA-125 and hypothyroidism.